THE COMPLIANCE OF CANADIAN AND AMERICAN FIRMS WITH DERIVATIVE REPORTING REQUIREMENTS - Cheng, Charles; Berry, Paul (Assurances)

(untitled) (HEC Montréal, 1999)
This paper attempts to uncover possible compliance issues of derivative reporting in Canada and the United States. A financial statement survey is perfomed to reveal areas where companies demonstrate unsatisfactory reporting, and where they meet the requirements of the accounting standards. Through the findings of the survey, certain potential problems are identified that accounting bodies may attempt to address in the future development of derivative accounting standards.